2020
DOI: 10.7717/peerj.8463
|View full text |Cite
|
Sign up to set email alerts
|

Unexpectedly high genetic diversity in a rare and endangered seabird in the Hawaiian Archipelago

Abstract: Seabirds in the order of Procellariiformes have one of the highest proportions of threatened species of any avian order. Species undergoing recovery may be predicted to have a genetic signature of a bottleneck, low genetic diversity, or higher rates of inbreeding. The Hawaiian Band-rumped Storm Petrel (‘Akē‘akē; Hydrobates castro), a long-lived philopatric seabird, suffered massive population declines resulting in its listing under the Endangered Species Act in 2016 as federally Endangered. We used high-throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…The ‘seabird paradox,’ or the contradiction between the high vagility of seabirds and their apparent reluctance to disperse among breeding sites 19 , has drawn attention to the scale of population genetic differentiation, the mechanisms driving differentiation, and the implications these factors have for seabird conservation 4 . The scale of population genetic structure varies extensively among studied seabird species, down to extremely small spatial and temporal distances 20 22 , although the scale to which we observed population structure in the Barau’s Petrel is finer and more robust than has previously been recognized or explored (Table 4 ). The three indices of genetic differentiation highlighted that the Barau’s Petrel colonies constitute clear and distinct genetic populations each containing a proportion of unique genetic material, despite being separated by only 5 km.…”
Section: Discussionmentioning
confidence: 71%
“…The ‘seabird paradox,’ or the contradiction between the high vagility of seabirds and their apparent reluctance to disperse among breeding sites 19 , has drawn attention to the scale of population genetic differentiation, the mechanisms driving differentiation, and the implications these factors have for seabird conservation 4 . The scale of population genetic structure varies extensively among studied seabird species, down to extremely small spatial and temporal distances 20 22 , although the scale to which we observed population structure in the Barau’s Petrel is finer and more robust than has previously been recognized or explored (Table 4 ). The three indices of genetic differentiation highlighted that the Barau’s Petrel colonies constitute clear and distinct genetic populations each containing a proportion of unique genetic material, despite being separated by only 5 km.…”
Section: Discussionmentioning
confidence: 71%
“…In some species of the Procellariiformes group, the patterns of genetic diversity have been explained as the consequence of either ecological (current) and/or evolutionary (historical) events (Antaky et al, 2020;Silva et al, 2016). In the first case, low diversity was associated with intense predation pressure observed in the Atlantic populations of Oceanodroma leucorhoa (Leach's Storm-Petrel), while high diversity was observed in the Pacific populations, which in turn were subject to less intense predation pressure (Bicknell et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Silva et al (2016) found evidence of genetic differentiation also using mitochondrial control region. The most recent study by Antaky et al (2020) (which used high-throughput sequencing) reported high levels of genetic diversity, with little differentiation between breeding colonies of the Hawaiian Band-rumped Storm-Petrel (Oceanodroma castro). Most of these examples found either strong and moderate evidence of genetic structure at large scales and regional scales, respectively (Antaky et al, 2020;Bicknell et al, 2012;Cagnon et al, 2004;Silva et al, 2016;Smith et al, 2007).…”
mentioning
confidence: 99%
See 2 more Smart Citations